Analysis of the Implementation of E-Government as An Effort to Reform the Public Service System in Indonesia - Vestu Rizqi Nugroho; Edi Hakim Ritonga; Muhammad Zul Hairil Aidil; Reza Syahputra Alfandi; Erinaldi Erinaldi (Civiliza Publishing, 2026)
This study aims to analyze the effectiveness of e-government implementation and its impact on public service reform in Indonesia. The rapid development of information technology has encouraged governments to adopt digital-based governance systems to improve service quality. However, various challenges still hinder optimal implementation. This research uses a qualitative approach with a literature review method by analyzing scientific journals, government reports, and policy documents related to e-government. The results indicate that e-government has significantly improved service efficiency, accessibility, transparency, and accountability. Digital-based services enable faster administrative processes and reduce bureaucratic complexity. However, the effectiveness of implementation is still uneven due to limitations in technological infrastructure, human resource competencies, and digital literacy among the public. In addition, system integration between government institutions remains a major challenge. The study concludes that e-government plays a crucial role in supporting public service reform, although continuous improvement is required to ensure equitable and optimal implementation. Strengthening infrastructure, improving human resource capacity, and enhancing system integration are essential strategies for maximizing the benefits of e-government in Indonesia.